ANALISA PENGLAMAN ANAK DIBAWAH UMUR YANG MENJADI KORBAN BULLYING DI LINGKUNGAN SEKOLAH - Messya Olla Savira; Qoni’ah Nur Wijayani (JOURNAL SAINS STUDENT RESEARCH, 2024)
Minors have mental conditions that are very vulnerable to events that interfere with their psychological condition such as bullying crimes that usually often occur in minors, who bully in general often their peers or schoolmates. Bullying crimes greatly affect the psyche that occurs against minors, this is because children still do not have strong protection in their mental mental condition. Bullying is a frightening scourge for minors because bullying very often occurs in schools and communities. Cases of bullying in Indonesia are also still very high, of course, every element should pay attention to these conditions, because the impact of bullying that occurs on minors is very heavy. Related to the impact of bullying crimes that occur against minors is very serious, from experiencing trauma to some who choose to end their lives. The problem of bullying must immediately take appropriate solution actions, from prevention to improvement, therefore the government must also play a role because bullying crimes have taken many victims, especially minors.